To Pretreat or Not to Pretreat: Prophylactic Anticholinergic Administration Before Dexmedetomidine in Pediatric Imaging. (August 2015) - Subramanyam, Rajeev; Cudilo, Elizabeth Maria; Hossain, Mohamed Monir; McAuliffe, John; Wu, Junzheng; Patino, Mario; Gunter, Joel; Mahmoud, Mohamed
Abstract : BACKGROUND: Dexmedetomidine (Dex) appears to be very effective as a sole sedative for pediatric imaging when used at high doses, but at an increased risk of transient hypertension, hypotension, and bradycardia. There are no clinical evidence/guidelines to guide anesthesia providers as to whether patients should be pretreated with an anticholinergic. The aim of this study was to demonstrate the changes in hemodynamic parameters after Dex sedation attributed to receiving or not receiving an anticholinergic pretreatment and compare for any differences or similarities. A subgroups analysis was performed in children with Down syndrome (DS). METHODS: In this retrospective descriptive study, we reviewed the records of 163 children receiving Dex anesthesia during MRI studies. Data analyzed included demographics, history of DS, and hemodynamics (heart rate [HR], systolic blood pressure [SBP], and diastolic blood pressure [DBP]) following Dex loading and infusion and the administration of an anticholinergic (atropine or glycopyrrolate). RESULTS: The mean age was 94.5 months, and 52 (32%) patients had DS. The generalized linear mixed-effects regression model showed a significant reduction in HR and SBP in all patients when no anticholinergic was administered compared with when it was administered. There was no significant change with DBP. During the scan period, the HR of the no-anticholinergic group decreased 26.6%, whereas that of the anticholinergic group decreased by only 16.7% from baseline ( P < 0.01). The maximal SBP increased by a significantly greater percentage, compared with baseline, in the anticholinergic group in comparison with the no-anticholinergic group (20.2% vs 10.4%, respectively; P = 0.02). In the DS group, the difference in the maximal SBP change during the scan period was exaggerated, with a percentage increase that was 36 times larger in the anticholinergic group compared with the no-anticholinergic group (22% vs 0.6%, respectively; P < 0.01). CONCLUSIONS: Administration of a prophylactic anticholinergic with Dex shows no advantage other than a transient clinically insignificant increase in HR and SBP, and it may precipitate transient exaggerated SBP in more patients compared with not using a prophylactic anticholinergic. Abstract : Supplemental Digital Content is available in the text.Published ahead of print April 11, 2015